Cryptocurrencies: The Revolution in the World Finance - Joshi, Sanjeev Kumar; Khatiwada, Nitesh; Giri, Jyoti (NCC Journal, 2018)
The cryptocurrency is thought to be the next internet revolution, where transactions are done utilizing peer-to-peer network creating a blockchain of the participants involved. Therefore, it is in totality creating a new virtual world, which might change the course of the foreseeable future finance. The reaction to the block chain and cryptocurrency is synonymous to the reaction to the internet when for the first time it emerged. While it is widely accepted for transactions in some countries; for instance in Nepal, it is illegal. Where the basic knowledge about the cryptocurrency is scarce in terms of Nepal, this article attempt to connote the grass root construct on cryptography, cryptocurrency and its practices across the globe to its readers.NCC JournalVol. 3, No. 1, 2018, page: 167-175